Cellulose–hemicellulose interactions at elevated temperatures increase cellulose recalcitrance to biological conversion. Issue 4 (6th February 2018) - Kumar, Rajeev; Bhagia, Samarthya; Smith, Micholas Dean; Petridis, Loukas; Ong, Rebecca G.; Cai, Charles M.; Mittal, Ashutosh; Himmel, Michael H.; Balan, Venkatesh; Dale, Bruce E.; Ragauskas, Arthur J.; Smith, Jeremy C.; et al.
Abstract : Hemicellulose–cellulose strong associations at elevated temperatures slows cellulose conversion significantly. Abstract : It has been previously shown that cellulose-lignin droplets' strong interactions, resulting from lignin coalescence and redisposition on cellulose surface during thermochemical pretreatments, increase cellulose recalcitrance to biological conversion, especially at commercially viable low enzyme loadings. However, information on the impact of cellulose–hemicellulose interactions on cellulose recalcitrance following relevant pretreatment conditions are scarce. Here, to investigate the effects of plausible hemicellulose precipitation and re-association with cellulose on cellulose conversion, different pretreatments were applied to pure Avicel® PH101 cellulose alone and Avicel mixed with model hemicellulose compounds followed by enzymatic hydrolysis of resulting solids at both low and high enzyme loadings. Solids produced by pretreatment of Avicel mixed with hemicelluloses (AMH) were found to contain about 2 to 14.6% of exogenous, precipitated hemicelluloses and showed a remarkably much lower digestibility (up to 60%) than their respective controls. However, the exogenous hemicellulosic residues that associated with Avicel following high temperature pretreatments resulted in greater losses in cellulose conversion than those formed at low temperatures, suggesting that temperature plays a strong role in the strength of cellulose–hemicellulose association. Molecular dynamics simulations of hemicellulosic xylan and cellulose were found to further support this temperature effect as the xylan–cellulose interactions were found to substantially increase at elevated temperatures. Furthermore, exogenous, precipitated hemicelluloses in pretreated AMH solids resulted in a larger drop in cellulose conversion than the delignified lignocellulosic biomass containing comparably much higher natural hemicellulose amounts. Increased cellulase loadings or supplementation of cellulase with xylanases enhanced cellulose conversion for most pretreated AMH solids; however, this approach was less effective for solids containing mannan polysaccharides, suggesting stronger association of cellulose with (hetero) mannans or lack of enzymes in the mixture required to hydrolyze such polysaccharides.